EFFECT OF TURMERIC (CURCUMA LONGA) ON OVERWEIGHT HYPERLIPIDEMIC SUBJECTS: DOUBLE BLIND STUDY - Pashine, Lekhani; Singh, J V; Vaish, A K; Ojha, S K; Mahdi, A A (Indian Journal of Community Health, 2012)
Objective: To evaluate the effect of turmeric (Curcuma longa) on serum lipid profile in overweight hyperlipidemic subjects. Methods: This was a double blind randomised control study. The study was conducted in the Department of Medicine, CSM Medical University, Lucknow from July 2010-June 2011. A total of 120 subjects were interviewed using a pre-tested semi-structured schedule whose BMI>25 and total cholesterol>200 mg/dl and/or triglyceride>150 mg/dl, were divided randomly using random number table into 2 groups Group-I (Aquous extract of Turmeric-1.4 gm per day) (n=53) and Group-II (Placebo) (n=52) for three months. They were given the same color capsules without revealing their identity, with the instructions to take the contents of each pack twice a day before meal for 90 days. Subjects were asked to give their 12 hour fasting blood samples on 0, 30, 60 and 90 day. The paired t-test was used to compare the changes amongst follow-ups and unpaired t-test was used to compare between groups. p-value<0.05 was considered as significant. Results: At the baseline, both the groups were similar in anthropometric and clinical parameters. Treatment group produced significant (p<0.0001) reduction in lipid profiles such as serum total cholesterol, triglyceride and LDL-cholesterol and VLDL- cholesterol in hypercholesteremic group from 0 day to 30, 60 and 90 day of follow-ups. However, there was no significant change in the placebo group. The percentage reduction was higher in the subjects of Turmeric group as compared to Placebo. Conclusion: Aquous extract of Turmeric has shown lipid lowering properties among overweight hyperlipidemic subjects.